(untitled) (Advancements in Homeopathic Research, 2022)
Background: Ehrenfried Pfeiffer and his colleagues have done much work on the utility and application of copper chloride crystallization test in disease diagnosis and the selection of homoeopathic similimum. By comparing the copper chloride crystal patterns, it is possible to arrive at disease diagnosis and remedy selection in a very cost effective way. Materials and methods: 10% copper chloride solution was crystallized with the serum of patients suffering from diabetes mellitus, osteoarthritis and chronic bronchitis by adding different remedies in different petri-dishes. These crystal patterns were compared with the crystal pattern of a healthy patient’s serum and graded based on the similarity. Most similar remedy based on this grading is compared with the symptoms similarity. Results: A total of 30 patients’ serum were collected, crystallized and compared for similarity in crystallization test and patient-remedy symptoms. Level of matching is as following: most similar - 6 (20%); moderately similar –15 (50%); least similar - 3 (10%); dissimilar symptoms – 1 (3.33%); dissimilar crystal pattern –5 (16.67%). More than two-third (70%) patients’ symptoms similarity matches with crystallization similarity. Conclusion: From the results of the present work one can conclude that the copper chloride crystallization test is reliable to arrive at the similimum in patients. Further studies are warranted for the administration of drugs selected by this method to the corresponding patients and to study their effectiveness in curing the diseases by continuous analysis. This methodology can be extended to a large number of patients to arrive at more conclusive results.